MORFOLOŠKE KARAKTERISTIKE UČENIKA PRVOG, DRUGOG I TREĆEG RAZREDA OSNOVNE ŠKOLE - Nevenka Zrnzević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The aim of this research was to establish the differences in some morphological characteristics between male students from the fi rst, second and third grade of primary school. 256 male students from the primary schools in Trstenik were tested for the research. Morphological characteristics were estimated according to three variables (body height, body weight and body mass index). The differences between male students of primary school were estimated according to the multivariant analysis of variance. The results of the research showed that, viewing from the aspect of morphological characteristics, there are differences between male students from the fi rst, second and third grade of primary school and they are statistically signifi cant.